Questions and Epistemic Stance in Contemporary Spoken British English - Zuczkowski, Andrzej (Cambridge Scholars Publisher, 2021)
This volume explores a model of epistemic stance, according to which speakers can communicate each single piece of information either as known/certain or uncertain or unknown. It presents a qualitative analysis of extracts from the Spoken British National Corpus 2014 to support the idea that questions come from two distinct epistemic positions: the Unknowing and the Uncertain; this latter ranges along two poles: Not Knowing Whether and Believing.In the epistemic continuum, Unknowing questions express a lack of knowledge and range from open to closed and dual wh-questions. On the other hand, Un.